Drugs to Be Used With a Filter for Preparation and/or Administration—2019. (April 2021) - Ipema, Heather J.; Zacher, Jessica M.; Galka, Eva; Nazari, Jonathan; Varabyeva, Alina; Yu, Michelle; Hartke, Patricia
This chart is an update to the 2012 article published in Hospital Pharmacy on injectable drugs to be used with a filter. To update the chart, drugs approved from December 2011 to April 2019 were reviewed to determine if they require filtration and drugs included in the 2012 table were reviewed for accuracy. Readers are urged to review national standards of practice for information about clinical situations that warrant the use of a filter for medication preparation or administration, independent of the drug being given, and the reader should consult the Food and Drug Administration (FDA)-approved prescribing information for the most up-to-date information.